KNOWLEDGE AND CHANGES IN BEHAVIOR REGARDING THE NON-PHARMACOLOGICAL TREATMENT OF THE SAH: BEFORE AND AFTER HEALTHEDUCATION PERFORMED BY A NURSE - Danusa Fernandes Severo; Simone Coelho Amestoy; Maira Buss Thofehrn; Silvia Goldmeier (Universidade Federal do Paraná, 2009)
Objective: to verify the knowledge about the non-pharmacological treatment of the SAH and the changes inbehavior regarding this type of treatment, before and after health education performed by a nurse, with patients with thehypertension diagnose that were submitted to hemodialysis. This was an exploratory and descriptive research, an actionresearch, of quantitative approach. It was divided in three stages: data collection, education in health, data gathering.Subjects were 19 patient with primary hypertension submitted to hemodyalisis sessions in a renal clinic of Torres-RS, fromOctober to December 2007. It was verified that the Education in Health performed by the nurse with hypertensive patientssubmitted to the hemodyalisis was positive, because it contributed to grant more knowledge to the patients about theirtreatment and also to behavioral changes regarding non-pharmacological treatment of the SAH, contributing to thesepatient's health promotion and also to their selfcare, contemplating the objectives of the Education in Health.